2012
DOI: 10.1589/jpts.24.1133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Virtual Reality Treadmill Training on Balance and Balance Self-efficacy in Stroke Patients with a History of Falling

Abstract: Abstract.[Purpose] The purpose of this study was to investigate the effects of virtual reality treadmill training on balance and balance self-efficacy in stroke patients with a history of falling.[Subjects] Twenty-one stroke patients with a history of falling were allocated into 2 groups: a virtual reality treadmill training group (experimental group, n = 11), and control group (n = 10). [Methods] We measured patients' balance function and balance self-efficacy before and after 3 weeks of virtual reality trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(115 citation statements)
references
References 32 publications
3
109
0
3
Order By: Relevance
“…Since VR training is characterised by individualised, high intensity training in a variety of virtual environments with a high amount of real-time feedback [13][14][15] it might be valuable in stroke rehabilitation. This is confirmed by recent studies [12,[15][16][17][18]. However, almost all studies on the effect of VR on balance and/or gait ability were conducted in the chronic phase after brain injury [9,12,16,17,[19][20][21][22][23].…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…Since VR training is characterised by individualised, high intensity training in a variety of virtual environments with a high amount of real-time feedback [13][14][15] it might be valuable in stroke rehabilitation. This is confirmed by recent studies [12,[15][16][17][18]. However, almost all studies on the effect of VR on balance and/or gait ability were conducted in the chronic phase after brain injury [9,12,16,17,[19][20][21][22][23].…”
Section: Introductionsupporting
confidence: 60%
“…This is confirmed by recent studies [12,[15][16][17][18]. However, almost all studies on the effect of VR on balance and/or gait ability were conducted in the chronic phase after brain injury [9,12,16,17,[19][20][21][22][23]. Because of the potential relevant characteristics of VR for motor learning and neuroplasticity [14], VR may be of even more added value during the earlier rehabilitation phase.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…[41][42][43][44][45][47][48][49][50][51][52][53][54][55][56] Hand searching did not identify any additional papers. The flow of studies through the review is shown in Figure 1.…”
Section: Flow Of Studies Through the Reviewmentioning
confidence: 99%
“…La recuperación del aparato locomotor fue medida antes y después de la intervención mediante resonancia magnética funcional y se aplicaron pruebas clínicas estandarizadas del equilibrio. Los hallazgos sugirieron que la rehabilitación con realidad virtual podría inducir la reorganización cortical ipsilateral y producir mejoras significativas en la función motora (45,46).…”
Section: Experiencias Terapéuticas En Accidente Cerebro Vascularunclassified